Integrated Whole Transcriptome Profiling and Bioinformatics Analysis for Revealing Regulatory Pathways Associated With Quercetin-Induced Apoptosis in HCT-116 Cells - Zhang, Zheyu; Li, Bin; Xu, Panpan; Yang, Bo (Frontiers in Pharmacology, 2019)
Quercetin (QUE) is a bioactive component belonged to the natural flavonoids group, and recent researchers found that it could against colorectal cancer (CRC). However, the exact mechanism by which QUE exerts its anti-tumor effects in CRC still remains unclear. In this study, MTS assay and ﬂow cytometry were used to detect the anti-tumor effects of QUE on HCT-116 cells. The results showed that QUE could inhibit the proliferation and induce apoptosis of HCT-116 cells. Furthermore, whole transcriptome sequencing was employed to establish the microRNA (miRNA), long non-coding RNA (lncRNA), circular RNA (circRNA) and mRNA profiles. A total of 240 differentially expressed lncRNAs (DElncRNAs), 131 circRNAs (DEcircRNAs), 83 miRNAs (DEmiRNAs), and 1415 mRNAs (DEmRNAs) were identified in the QUE-treated HCT-116 cells compared to the untreated HCT-116 cells. Then, quantitative real-time polymerase chain reaction (qRT-PCR) was used to validate the expression of selected circRNAs, miRNAs, lncRNAs and mRNAs. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis were performed to further investigate RNAs’ biological functions and potential mechanisms. Based on the theory of competing endogenous RNA (ceRNA), the circRNA-miRNA-mRNA and lncRNA-miRNA-mRNA regulatory networks were constructed to illustrate the regulatory relationship between non-coding RNA (ncRNA) and mRNA. Our results provided novel information about the molecular basis of QUE in treating CRC. Our findings indicated that deep RNA sequencing analysis of mRNA and ncRNAs was a promising approach to research the mechanisms of anticancer.